The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1007/s00438-008-0398-2
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metal and abiotic stress inducible metallothionein isoforms from Prosopis juliflora (SW) D.C. show differences in binding to heavy metals in vitro

Abstract: Prosopis juliflora is a tree species that grows well in heavy metal laden industrial sites and accumulates heavy metals. To understand the possible contribution of metallothioneins (MTs) in heavy metal accumulation in P. juliflora, we isolated and compared the metal binding ability of three different types of MTs (PjMT1-3). Glutathione S-transferase fusions of PjMTs (GSTMT1-3) were purified from Escherichia coli cells grown in the presence of 0.3 mM cadmium, copper or zinc. Analysis of metal bound fusion prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(45 citation statements)
references
References 40 publications
3
40
0
2
Order By: Relevance
“…under the conditions of water deficit the endogenous amount of abscisic acid enhances which prevents the water loss through transpiration by decreasing the size of stomatal aperture. Increase in the content of abscisic acid under Zn and Cu stresses increased the metalothionenins content in Prosopis juliflora, thereby helped in the managing the heavy metal stress in the plants [35]. In the present study the seed pre-soaking treatment of 24-EpiBR increased the relative abundance of abscisic acid in B. juncea plants as compared to the control.…”
Section: -Epibrassinolide Mediated Regulation Of Endogenous Contentsupporting
confidence: 52%
“…under the conditions of water deficit the endogenous amount of abscisic acid enhances which prevents the water loss through transpiration by decreasing the size of stomatal aperture. Increase in the content of abscisic acid under Zn and Cu stresses increased the metalothionenins content in Prosopis juliflora, thereby helped in the managing the heavy metal stress in the plants [35]. In the present study the seed pre-soaking treatment of 24-EpiBR increased the relative abundance of abscisic acid in B. juncea plants as compared to the control.…”
Section: -Epibrassinolide Mediated Regulation Of Endogenous Contentsupporting
confidence: 52%
“…The resulting proteins are able to bind these metals efficiently. Thus, MTs appear to participate in metal homeostasis, mechanisms leading to tolerance to high concentrations of metals, and antioxidant defence mechanisms (Cobbett and Goldsbrough, 2002;Guo et al, 2008;Usha et al, 2009). Furthermore, Mir et al (2004) have demonstrated that metallothionein type 2-like is actively transcribed in Quercus suber cork cells in response to oxidative stress, both as a free radical scavenger, via its sulfhydryl groups and as a copper chelator.…”
Section: Discussionmentioning
confidence: 99%
“…4). Previously it has been found in MT gene promoters in T. aestivum (Giritch et al, 1998), Hordeum vulgare (Ozturk et al, 2002, P. juliflora (Usha et al, 2009), E. guineensis (Omidvar et al, 2010) andP. coarctata (Usha et al, 2011).…”
Section: Lightmentioning
confidence: 99%
“…Analyses of type 3 metallothionein gene promoters in Populus alba (MT3b) (Bereta et al, 2009), Elaeis guineensis (MT3-B) (Siti Nor Akumar et al, 2002) and Porteresia coarctata (PcMT3) (Usha et al, 2011) revealed the presence of MREs. Usha et al (2009) described the sequences of three Prosopis juliflora MTs that do not contain the MRE motif within the promoter region. In the MT3 gene of Citrus unshiu the MRE sequence does not occur either, and the expression of this gene does not change under the influence of heavy metal ions (Endo et al, 2007).…”
Section: Identification Of Putative Cis Elements Connected With the Pmentioning
confidence: 99%